The Assessment Of The Relationship Between Organizational Performance And Innovation Management Capacity - Niken Savitri Primasari; Zainul Wasik; Achmad Saiful Ulum; Dominicus Wahyu Pradana (PT. Mawadaku Sukses Solusindo, 2024)
This study aims to explore how capability to manage innovation affects the functioning of organizations. This study explores the question, How much do emotional and intellectual resources affect marketing management competence, which directly affects an organization's performance? using the resource-advantage theory as its foundation. Fifty managers and academics from different multinational organizations participated in in-depth interviews to gather data for the research objectives, and fresh empirical insights were provided. Digital technology, skill, and knowledge are among the constituents of intellectual and emotional assets were identified in this study along with their effects on business performance. The study's ability to be broadly applied is restricted by its emphasis on small and medium-sized businesses (SMEs). Future studies in different sectors and countries should be carried out to examine the relationships reported in this study. This work contributes to the body of knowledge on sustainability by creating a conceptual model that explains how innovation management evolved, its function in the market, and the results that sustainability management produces in tandem. The findings are significant to policymakers as well as SMEs. There is a definite need to look into how organizations might use these talents to their advantage in order to grow.